Studying Phraseology as One of the Methods of Teaching the Russian Language - Rasulov Ilkhom Inamovich (Researchparks Publishing, 2022)
The article examines phraseology from a methodological point of view. The study of phraseological units in accordance with lexico-semantic fields is one of the effective methods of teaching the Russian language.